The Impacts of Surgery and Intracerebral Electrodes in C57BL/6J Mouse Kainate Model of Epileptogenesis: Seizure Threshold, Proteomics, and Cytokine Profiles - Tse, Karen; Beamer, Edward; Simpson, Deborah; Beynon, Robert J.; Sills, Graeme J.; Thippeswamy, Thimmasettappa (Frontiers in Neurology, 2021)
Intracranial electroencephalography (EEG) is commonly used to study epileptogenesis and epilepsy in experimental models. Chronic gliosis and neurodegeneration at the injury site are known to be associated with surgically implanted electrodes in both humans and experimental models. Currently, however, there are no reports on the impact of intracerebral electrodes on proteins in the hippocampus and proinflammatory cytokines in the cerebral cortex and plasma in experimental models. We used an unbiased, label-free proteomics approach to identify the altered proteins in the hippocampus, and multiplex assay for cytokines in the cerebral cortex and plasma of C57BL/6J mice following bilateral surgical implantation of electrodes into the cerebral hemispheres. Seven days following surgery, a repeated low dose kainate (KA) regimen was followed to induce status epilepticus (SE). Surgical implantation of electrodes reduced the amount of KA necessary to induce SE by 50%, compared with mice without surgery. Tissues were harvested 7 days post-SE (i.e., 14 days post-surgery) and compared with vehicle-treated mice. Proteomic profiling showed more proteins (103, 6.8% of all proteins identified) with significantly changed expression (p < 0.01) driven by surgery than by KA treatment itself without surgery (27, 1.8% of all proteins identified). Further, electrode implantation approximately doubled the number of KA-induced changes in protein expression (55, 3.6% of all identified proteins). Further analysis revealed that intracerebral electrodes and KA altered the expression of proteins associated with epileptogenesis such as inflammation (C1q system), neurodegeneration (cystatin-C, galectin-1, cathepsin B, heat-shock protein 25), blood–brain barrier dysfunction (fibrinogen-α, serum albumin, α2 macroglobulin), and gliosis (vimentin, GFAP, filamin-A). The multiplex assay revealed a significant increase in key cytokines such as TNFα, IL-1β, IL-4, IL-5, IL-6, IL-10, IL12p70, IFN-γ, and KC/GRO in the cerebral cortex and some in the plasma in the surgery group. Overall, these findings demonstrate that surgical implantation of depth electrodes alters some of the molecules that may have a role in epileptogenesis in experimental models.